PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN JOB RELEVANT INFORMATION SEBAGAI VARIABEL MODERATING - Usman Rahman; Basri modding; Amiruddin Amiruddin (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2020)
This study aims to determine and test empirically the influence of budgetary participation on managerial performance with Job Relevant Information as a moderating variable. The variables used in this research are the participation of budget preparation as independent variable, and Job Relevant Information as moderating variable, while the implementation of managerial performance as dependent variable. This study uses quantitative methods because it emphasizes the testing of theories through the measurement of research variables with and perform data analysis with statistical procedures. The type of data used in this study is the primary data. Primary data was obtained from the distribution of questionnaires to several OPD Kabupaten Pinrang. Sampling method used is by using the sampling formula with the sample obtained as many as 176 respondents. Hypothesis testing was done by using multiple regression statistic test and regression analysis of moderation with residual approach. The results showed that the participation of budget preparation has a positive and significant effect on managerial performance. Based on criteria of moderating variable from result of MRA, job relevant information in this research is moderating variable. Job relevant information strengthens the relationship between budgetary participation with managerial performance as seen from t test result and anova test after input interaction variable, it is known that probability significance above 0,05 is significant.